Determinan Minat Penggunaan Paylater pada Masyarakat Kota Surakarta: Peran Literasi Keuangan dan Inklusi Keuangan - Berlian Eva Yoruna; Umi Hanifah; Indra Hastuti (Pusat Riset dan Inovasi Nasional, 2026)
The rapid development of financial technology has led to the increasing use of paylater as an alternative digital payment method. The convenience of access and the speed of transactions have made paylater increasingly popular among the public. However, its use requires adequate financial literacy and access to formal financial services to ensure responsible financial decision-making. This study aims to analyze the factors influencing the intention to use paylater among the people of Surakarta city by examining the roles of financial literacy and financial inclusion. A quantitative approach was employed using primary data collected through an online questionnaire distributed via Google Forms. The sampling technique used was purposive sampling, resulting in a total of 100 respondents. The data were analyzed using multiple linear regression with SPSS Statistics 25 software. The research results indicate that financial literacy and financial inclusion influence the intention to use paylater services among the residents of Surakarta. The findings suggest that improving financial literacy and expanding financial inclusion can encourage individuals to make more appropriate financial decisions in using paylater services, enabling them to utilize these services according to their financial needs and capabilities.